A Survey of Teachers’ Status in Mental Health Education Management Based on Big Data Analysis - Yuxi Wang; Chunmei Xue; Minmeng Zhang (Occupational Therapy International)
This paper uses the theory of mental health education to conduct an in-depth study and analysis of teachers’ educational management, and based on this, it designs a survey method on teachers’ status and analyzes its strategic methods based on the results of the survey. Using literature analysis, questionnaires, survey interviews, and statistical analysis, the analysis of mental health of primary and secondary school teachers in the city was made. The results of the survey and analysis of the questionnaire results were used to construct a compatible mental health evaluation model. It was found that the overall level of elementary school teachers’ mental health is poor at present, and different levels of mental health were presented with school sections and ages. A total of 286 questionnaires were distributed, 278 valid questionnaires were returned, and statistical analysis was conducted using EXCEL tables based on the collected data. The data analysis results show that the mental health level of teachers in middle school is significantly lower than that of teachers in primary school, and the mental health level of teachers in primary and secondary schools decreases with the increase of age. Therefore, to prevent the small and the gradual, start from the source; do a good job in the publicity of mental health education in peacetime; popularize the knowledge of mental health, so that teachers have a correct understanding of mental health education; improve the professional level of teachers; set up professional teachers in professional positions; establish sound job system and evaluation system, etc. Promote the balanced development of school psychological counseling rooms, strengthen the construction of professional teachers in mental health education, improve various systems of mental health education, comprehensively popularize teachers’ mental health education and training, and mobilize teachers’ enthusiasm for scientific research on mental health education. Improve the understanding of mental health education in colleges and universities, and regard mental health education as the foundation of all education.